"Evaluation of Relation between Mercury Concentration in Saliva with Number and Surfaces of Amalgam Fillings " - F. Agha Hosseini; P. Begianian Vaziri (Tehran University of Medical Sciences, 2004)
Statement of Problem: Amalgam is the most widely used dental restorative material. However, because of continuous low-level release of Mercury from amalgam fillings, its safety has been questionable. Purpose: The aim of this study was the evaluation of concentration of Mercury in saliva before and after amalgam fillings and its relation with numbers and surfaces of amalgam fillings. Materials and Methods: In an analytic interventional study we surveyed concentration Mercury in saliva before and after amalgam fillings. Twenty-five Patients (9 male, 16 female) who referred to oral medicine department of Tehran university of medical science and Haj- Abdol- Vahab medical center who had no amalgam fillings were selected and the samples of saliva (5cc) was collected before fillings. After that all of posterior decayed teeth were filled in an appointment with amalgam and, 24 hours later, the second samples of saliva (5cc) was collected. The amount of saliva Mercury before and after filling was measured and its difference was analyzed by paired t- test. Results: In this study the mean of Mercury in saliva was 0.00896 µg/ml before and 0.16404 µg/ml after amalgam fillings. The mean of number of fillings was 1.96 and mean of size of surfaces was 76.43 mm2 and mean of consumption amalgam was 4.1 units. Conclusion: There was no significant correlation between age (P=0.677), sex, number of fillings (P=0.055), number of surface of filling (P=0.059) and size of surfaces of fillings (P=0.072), with Mercury levels in saliva after amalgam fillings. There was a significant relation between Mercury level of saliva after fillings and amalgam amount (P= 0.036). Therefore amalgam may be designate a significant source for Mercury release in saliva. Since this is a preliminary study, it needs supplementary evaluations in saliva, blood and urine in different periods after amalgam fillings.